High CXCR3 on Leukemic Cells Distinguishes IgHVmut from IgHVunmut in Chronic Lymphocytic Leukemia: Evidence from CD5high and CD5low Clones - Gayane Manukyan; Tomas Papajik; Zuzana Mikulkova; Renata Urbanova; Veronika Smotkova Kraiczova; Jakub Savara; Milos Kudelka; Peter Turcsanyi; Eva Kriegova (Journal of Immunology Research)
Despite the shared pattern of surface antigens, neoplastic cells in chronic lymphocytic leukemia (CLL) are highly heterogeneous in CD5 expression, a marker linked to a proliferative pool of neoplastic cells. To further characterize CD5high and CD5low neoplastic cells, we assessed the chemokine receptors (CCR5, CCR7, CCR10, CXCR3, CXCR4, CXCR5) and adhesion molecules (CD54, CD62L, CD49d) on the CD5high and CD5low subpopulations, defined by CD5/CD19 coexpression, in peripheral blood of CLL patients (n=60) subgrouped according to the IgHV mutational status (IgHVmut, n=24; IgHVunmut, n=36). CD5high subpopulation showed a high percentage of CXCR3 (P<0.001), CCR10 (P=0.001), and CD62L (P=0.031) and high levels of CXCR5 (P=0.005), CCR7 (P=0.013) compared to CD5low cells expressing high CXCR4 (P<0.001). Comparing IgHVmut and IgHVunmut patients, high levels of CXCR3 on CD5high and CD5low subpopulations were detected in the IgHVmut patients, with better discrimination in CD5low subpopulation. Levels of CXCR3 on CD5low subpopulation were associated with time to the next treatment, thus further confirming its prognostic value. Taken together, our analysis revealed higher CXCR3 expression on both CD5high and CD5low neoplastic cells in IgHVmut with a better prognosis compared to IgHVunmut patients. Contribution of CXCR3 to CLL pathophysiology and its suitability for prognostication and therapeutic exploitation deserves future investigations.